Impact of Forced Marriage on Young Women in Bades Village, Pasirian, Lumajang - Ainiyah, Qurrotul; Nisah, Yulia (JASNA : Journal For Aswaja Studies, 2025)
Forced marriage has been identified as one of the primary causes of marital failure. This study aims to delve into the social, cultural, and economic factors that drive the practice of forced marriage in the Bades community. Employing a case study approach, this research reveals the following: Firstly, the tradition of arranged marriages without the consent of the child is common among the mountainous people of Bades, leading to the stigmatization of unmarried women over the age of 18 as "old maids". Secondly, forced marriage has a detrimental impact on women, including psychological distress, loss of educational opportunities, limited career prospects, marital discord, domestic violence, and economic instability. Although some forced marriages endure, the majority of women in Bades face hardships and suffering due to pressure from their families.